UPAYA MENCEGAH PERNIKAHAN DINI MELALUI SOSIALISASI BAHAYA PERNIKAHAN DINI PADA PELAJAR DI DESA LINGSAR - Kushartawan, Patih; Hamdi, Muhammad Alwi; Nurulita, Ainaya Fatimah; Syafnita, Nabila Ulfa; Kurniawati, Esy; Arjuna, Arjuna; Fadhilah, Nurul; Putri, Yolanda; Syafiuddin, Muhammad; Abiyyu, Muhammad Farras (Jurnal Wicara, 2023)
Early marriage is a phenomenon that should be of concern to all groups. Indonesia itself is a country that ranks 8th in the world and ranks 2nd in ASEAN with a total of almost 1.5 million cases of early marriage. Early marriage also has many negative impacts on the perpetrators. One area in Indonesia that has a vulnerability to early marriage is Lingsar Village, where the perpetrators of early marriage in Lingsar Village are still students. This socialization activity aims to provide understanding to students in Lingsar Village about the dangers of early marriage. This activity was carried out using the socialization method which targeted students who were still in junior and senior high school in Lingsar Village. The result of this activity is that students understand the dangers of early marriage which is shown from the disinterest of students to marry at a young age and the enthusiasm of students in participating in socialization activities. Thus, this activity can be said to be successful in providing understanding to students in Lingsar Village.